Renal Stones and Their Medical Management - Smith, E. Kinsey M. (1978)
Renal stones are common; in North America calcific stones far exceed uric acid and cystine stones in number. Patients with recurrent, complicated, or bilateral stones merit thoughtful investigation which should take into account what is known about the causes of stone. This review gives an outline of investigation and therapy for cystine and uric acid stones on the assumption that they can be dissolved and recurrences prevented. The challenge of calcific stones is faced and the use of thiazide and allopurinol is discussed as a potentially useful approach to treatment.